The Development of Pteridophyte Catalog of Curug Lawe Petungkriyono as Learning Source for Senior High School Students - Husna, Destri Nurul; Ngabekti, Sri; Abdullah, Muhammad (Journal of Biology Education, 2018)
This research aims to identify the variety of fern species in Curug Lawe area of Techno-forestry Park, Petungkriyono; then develop the catalog, investigate the validity and analyze the effectiveness of the catalog as Biology learning source for senior high school students. The study was done in Curug Lawe Petungkriyono as exploration place and SMA N 1 Petungkriyono for validity test. The design of catalog used Sugiyono (2012) and research method for effectiveness test is One-Shoot Study Case. The object of study is all fern plants found through the way to Curug Lawe. The research result shows that percentage of catalog validity by expert and biology teacher is 94.5%. The percentage of students’ classical completeness of students’ learning results is 78%, while percentage of incomplete students is 22%. The mean of students’’ response questionnaire after the learning is 83% with very good criteria. Generally, teacher and students give positive and very good response toward the applied learning. The conclusion of this research is Pteridophyte Catalog is proper and effective to be used as Biology learning source for senior high school students.